EGFR phosphorylates DNAJB1 to suppress α-synuclein aggregation in Parkinson’s disease - Yun-Yu Huang; Sue-Jane Lin; Wei-Yu Chiang; Yuan-Teng Chang; Chan-Chih Yang; Chia-Yu Liao; Ya-Lan Chang; Chin-Hsien Lin; Shu-Chun Teng (npj Parkinson's Disease)
Abstract Parkinson’s disease (PD), characterized by α-synuclein accumulation in dopaminergic neurons, is a common neurodegenerative disorder. Recent findings highlight DNAJB1 as a crucial factor in the disaggregation of α-synuclein fibrils in vitro, yet the underlying mechanisms and regulatory processes in neuronal cells remain largely undefined. This study reveals that DNAJB1 facilitates the clearance of α-synuclein via the Hsp70 chaperone system. Phosphorylation of DNAJB1 at tyrosine 5 by the epidermal growth factor receptor (EGFR) is essential for mitigating α-synuclein aggregation, enhancing its interaction with Hsp70. Dysregulation of this pathway disrupts α-synuclein delivery to Hsp70, worsening aggregation in neuronal cells. Analysis of human brain lysates from individuals with PD and unaffected controls showed reduced levels of EGFR and DNAJB1, with an increase in phosphorylated DNAJB1 at Y5. These findings elucidate mechanisms in PD pathology and suggest DNAJB1 as a promising candidate for targeted therapeutic strategies.